Gambaran Kejadian Hipotensi Paska Anestesi Spinal Pasien Seksio Sesarea di RSIA Ummu Hani Purbalingga - Dwi Atika Safitri; Dwi Novitasari; Wilis Sukmaningtyas (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Sectio caesarea is a method of delivery by surgery. Spinal anesthesia is given before surgery begins. Spinal anesthesia has a side effect in the form of hypotension caused by dilation of blood vessels. Hypotension occurs as much as 16% - 33% in the world, while the incidence of hypotension in RSIA Umm Hani Purbalingga is estimated to occur as much as 50%. This study aims to determine the picture of hypotension in RSIA Umm Hani Purbalingga. This study uses descriptive observational method with retrospective approach. Population of 356 and a sample of 78 respondents. Samples were taken by purposive sampling method, the data used is secondary data (medical records). Respondents were grouped into 3 factors affecting hypotension. Respondents with the most hypotension as follows, aged 26-35 years (25.64 %), from the preloading fluid administration Group (48.72%), and the long fasting group >6 hours (30.77%). Subsequent studies researchers advise to take data from primary and secondary sources, pay attention to blood pressure before anesthetic injection, and minutes to what hypotension occurs.